2010
DOI: 10.1038/msb.2010.92
|View full text |Cite
|
Sign up to set email alerts
|

Coupling governs entrainment range of circadian clocks

Abstract: Circadian clock oscillator properties that are crucial for synchronization with the environment (entrainment) are studied in experiment and theory.The ratio between stimulus (zeitgeber) strength and oscillator amplitude, and the rigidity of the oscillatory system (relaxation rate upon perturbation) determine entrainment properties. Coupling among oscillators affects both qualities resulting in increased amplitude and rigidity.Uncoupled lung clocks entrain to extreme zeitgeber cycles, whereas the coupled oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
467
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(503 citation statements)
references
References 85 publications
33
467
0
3
Order By: Relevance
“…The SCN molecular clock communicates with peripheral tissues, such as skeletal muscle, using neurohumoral, metabolic, and temperature signals (49)(50)(51). In our in vivo study, core clock alignment was demonstrated by plasma cortisol and melatonin profiles, as well as by muscle core clock gene expression (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…The SCN molecular clock communicates with peripheral tissues, such as skeletal muscle, using neurohumoral, metabolic, and temperature signals (49)(50)(51). In our in vivo study, core clock alignment was demonstrated by plasma cortisol and melatonin profiles, as well as by muscle core clock gene expression (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Figure 1 shows a schematic state diagram of self-sustained oscillators. Arnold tongues of circadian clock models such as the Poincaré or the Gonze oscillator [32] can be found in references [30,33] and [34], respectively. Some of the desynchronized oscillatory dynamics illustrated in figure 1 have been observed in a variety of organisms under the respective conditions [35].…”
Section: The Periodically Forced Oscillatormentioning
confidence: 99%
“…7 Ancak; fibroblast, karaciğer, böbrek ve akciğeri kapsayan periferal osilatör-ler sıcaklık değişimine oldukça hassastır. 23 J Je et t--L La ag g; farklı zaman bölgeleri arasındaki seyahati tanımlar. Yolculuk sonucu iç saat ile varış yerindeki aydınlık/karanlık döngüsü arasındaki uyuşmazlık birtakım sorunlara yol açabilmektedir.…”
Section: Si̇rkadi̇yen Ri̇tmi̇n Transkri̇psi̇yonel Ve Translasyonel Mekani̇zmasiunclassified